Depression 2017
DOI: 10.5772/67064
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression in Cardiovascular Surgery

Abstract: Although anxiety and depression are psychological risk factors for coronary artery disease (CAD), psychological aspect in patients with cardiovascular surgery has been less considered. Cognitive and psychological deficit has been still concerning in spite of notable improvement of cardiovascular surgery using cardiopulmonary bypass perfusion. The purpose of this chapter review is to discuss recent data concerning the prevalence and trend of anxiety and depression of patients with cardiovascular surgery and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…But in same season bulk tank somatic cell count (BTSCC × 1000 cells/ml) was found as 469 ± 113.4 (Mean ± SEM) [68]. In a study with raw milk in winter and summer In Slovenia, total bacteria count was found higher than 100,000 cfu/ml [69].…”
Section: Bacterial Contaminants In Conventional Animal Productsmentioning
confidence: 91%
See 1 more Smart Citation
“…But in same season bulk tank somatic cell count (BTSCC × 1000 cells/ml) was found as 469 ± 113.4 (Mean ± SEM) [68]. In a study with raw milk in winter and summer In Slovenia, total bacteria count was found higher than 100,000 cfu/ml [69].…”
Section: Bacterial Contaminants In Conventional Animal Productsmentioning
confidence: 91%
“…In a study conducted in Slovenia, 95.0% of raw milk that was collected during winter and summer contains yeast and 63.3% contains molds. Isolated mold strains were identified as Geotrichum (51.5%), Aspergillus (33.8%), Mucor (5.9%), Fusarium (2.9%) and Penicillium (2.9%) genuses [69].…”
Section: Fungal Contaminants and Mycotoxins In Conventional Animal Prmentioning
confidence: 99%
“…As many as 25% of subjects who were CABG patients experienced anxiety and 21.2% of subjects experienced depression. 6 Meanwhile, in another study, it was found that the degree of depression and anxiety in valve replacement patients was lower than in CABG. This may be because the pathophysiology of valvular heart disease is not influenced by psychological factors, while coronary heart disease is closely related.…”
Section: Introductionmentioning
confidence: 98%
“…Depression is known as a predictor of the incidence of heart disease, while anxiety is known as a factor that increases the risk of mortality and morbidity before cardiac surgery procedures. 6 Socio-demographic data such as age, gender, marital status, occupation, and education, as well as medical data such as underlying diseases, comorbidities, the procedure of open-heart surgery, and depression as well as anxiety scores were taken as subject characteristics. Depression and anxiety were determined using the Zung Selfrating Depression Scale (Z-SDS) and Zung Selfrating Anxiety Scale (Z-SAS) questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…Despite strict regulations for the monitoring of chemical residue, the possible contamination of food of animal origin through industrial and agricultural activities remains a major problem worldwide (Okamoto & Motomura, 2017). Health risks will depend on the eating habits of each individual, the level of contamination, different types of products used in the diet and the portion size.…”
Section: Introductionmentioning
confidence: 99%